2022
DOI: 10.3389/fenrg.2022.1015465
|View full text |Cite
|
Sign up to set email alerts
|

An eco-technoeconomic analysis of hydrogen production using solid oxide electrolysis cells that accounts for long-term degradation

Abstract: This paper presents an eco-technoeconomic analysis (eTEA) of hydrogen production via solid oxide electrolysis cells (SOECs) aimed at identifying the economically optimal size and operating trajectories for these cells. Notably, degradation effects were accounted by employing a data-driven degradation-based model previously developed by our group for the analysis of SOECs. This model enabled the identification of the optimal trajectories under which SOECs can be economically operated over extended periods of ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The objective of this work will be to introduce the degradations in a simple and linear way, considering the long degradation studies found in the literature. For this purpose, the recent degradation works of Naeini et al [30,31] have been taken as reference.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this work will be to introduce the degradations in a simple and linear way, considering the long degradation studies found in the literature. For this purpose, the recent degradation works of Naeini et al [30,31] have been taken as reference.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Among these methods, solid oxide electrolysis cells (SOECs) in water electrolysis technology operate at relatively high temperatures and have demonstrated potential for more efficient hydrogen production compared to alkaline and polymer electrolysis systems. [4][5][6][7] While numerous studies have reported the high performance of water electrolysis, ensuring the long-term stability of SOECs remains a challenge. 8 Efforts to mitigate degradation are crucial for developing highly efficient water electrolysis systems.…”
Section: Introductionmentioning
confidence: 99%
“…[11] proposed integrated systems for the use of large-scale floating wind farms dedicated to hydrogen generation. [12] developed an eco-technoeconomical analysis approach to evaluate hydrogen generation using solid oxide electrolysis cells (SOECs), including their long-term degradation. They showed that LCOH from SOECs are in the range $2.78/kg to $11.67/kg compared to grey hydrogen, where LCOH varies between $1.03/kg and $2.16/kg, and they furthermore concluded that the electricity price was more dominant than the capital costs in these results.…”
Section: Introductionmentioning
confidence: 99%